Atelier 3. (Amsterdam : Stedelijk Museum Amsterdam, 1966)
Aerssens, Charles ; Anna ; Asselbergs, Gustave ; Bonies, Bob ; Boots, Jacob ; Cardena ; Huismans, Sipke ; Lennarts, Johan ; de Boer Lichtveld, Frans ; van Munster, Jan ; Peeter, Zoltin ; Smeets, Jan Willem
biog., tent. per kunstenaar
Atelier 3, Stedelijk Museum Amsterdam, 22 april - 22 mei 1966
Nederlands
boek